Tissue Factor–Bearing Microparticles and Thrombus Formation - Zwicker, Jeffrey I.; Trenor, Cameron C.; Furie, Barbara C.; Furie, Bruce (Arteriosclerosis, thrombosis, and vascular biology, 2011)
Blood microparticles are vesicular structures with a diameter of 100 to 1000 nm that are present in the blood of normal subjects and in patients with various diseases. These microparticles are derived from cells that circulate in the blood and cells associated with the blood vessel wall. Microparticle membranes retain the protein receptors of their parent cells and may retain RNAs and other cytosolic content. On the basis of surface protein expression, microparticles are known to be derived from platelets, granulocytes, monocytes, endothelial cells, smooth muscle cells, and tumor cells. Only a subpopulation of these microparticles expresses tissue factor.